“Nyiwak” dalam Kostum Kematian Masyarakat Lombok dalam Perspektif Hukum Islam - Akmal, Haerul; Islam, Muhammad Thoriqul; Marjany, Nawa (Transformatif, 2024)
Islam is a religion adhered to by most of Lombok’s population. Lombok is an area rich in religious traditions. One of them in the Praya area is the ‘Nyiwak’ tradition. Nyiwak is a religious tradition of dhikr and tahlil carried out on the ninth day of a person’s death. This “Nyiwak” tradition applies to all levels of society regardless of the economic level of the family left behind. This tradition is difficult for the people of Praya to abandon because it is ingrained and has become a forum for friendship between communities. In addition, this tradition is also one of their ancestors’ legacies, which continues to be preserved to this day. Thus, some view it as a heresy (bid’ah). Therefore, this research aims to analyze the Nyiwak tradition based on an Islamic law perspective. This research was a descriptive analysis research, where the researcher tried to describe the concept of the Nyiwak tradition in Praya globally and then analyzed it based on Islamic law. Data was collected through participant observation by being one of the congregation readers of Yasin, dhikr, and Tahlil at the forum. The research results obtained two views about Islamic law’s “Nyiwak” tradition. Firstly, the research revealed that it was not based on the Sunnah of the Prophet or Bid’ah Dholalah. Secondly, this tradition was Bid’ah Mahmudah or praiseworthy, because it contained good habits to bring one’s soul closer to Allah SWT.